PSYCHOLOGICAL STUDY OF THEMES IN TONI MORISON’S THE BLUEST EYE THROUGH INFERIORITY COMPLEX - Zanyar Kareem Abdul (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
Toni Morrison’s The Bluest Eye (1970) is one of the controversial modern American novels. She is a Noble Prize winner whose works are praised for addressing the harsh consequences of racism and colour issue in America. The story is written during 1941, the Great Depression in which a black family suffers from poverty, colour skin, and familial issues. Pecola Breedlove, as the protagonist, suffers from Inferiority Complex in a dysfunctional family whose desire is to have white skin and blue eyes.  The inferiority complex theory was taken from Alfred Adler, whose works are significantly backbone in the world of psychology. The aims of this research are to analyse the personality of Pecola through which she searches for an ideal beauty as a black female character in the novel and to demonstrate the impact of racist attitude and incestuous relationship within a family. The research result shows that Pecola’s lives provide an example of the pain which results from facing Inferiority Complex on which she never sees herself as a complete image of being. It is somewhat broken and lacks self-esteem through which she was seen as a mad woman in the attic.